Balinese Instrument Music Improve the Growth and Productivity of PakcoyMustard Plant (Brassica rafa L.) - Gautama, Dewa Putu Yoga Gautama; Wijaya, I Made Anom S.; Budisanjaya., IPutu Gede Budisanjaya. (Jurnal BETA (Biosistem dan Teknik Pertanian), 2018)
<article class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:fae0572e-2e95-430f-987d-0f9e7639e3e5-34" data-testid="conversation-turn-70" data-scroll-anchor="true" data-turn="assistant"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="a6cceedb-56eb-44af-94d5-44bac478c951" data-message-model-slug="gpt-5-mini"> High-frequency sound waves can stimulate leaf stomata to remain open, improving the efficiency of fertilizer absorption. This research aimed to determine (1) the effect of Balinese instrumental music on the growth and productivity of pakcoy mustard plants, and (2) the type of Balinese instrumental music that provides the best growth and productivity. Treatments involved applying Balinese music with different musical nuances for three hours: Treatment 1 used Angklung music, Treatment 2 used Semarpagulingan music, and Treatment 3 used Gong Kebyar music. Data were analyzed using ANOVA in IBM SPSS 20. Observed variables included plant height, canopy area, green leaf level, and dry weight. The results showed that Gong Kebyar music produced the highest values in all variables: plant height of 29.98 cm, canopy area of 1684 cm², dry weight of 68.61 g, and green leaf level of 186.79. The application of Balinese instrumental music positively affected pakcoy mustard growth, with Gong Kebyar music yielding the best overall growth across all observed variables.